2012
DOI: 10.1371/journal.pone.0031732
|View full text |Cite
|
Sign up to set email alerts
|

Primary Effusion Lymphoma Cell Death Induced by Bortezomib and AG 490 Activates Dendritic Cells through CD91

Abstract: To understand how cytotoxic agent-induced cancer cell death affects the immune system is of fundamental importance to stimulate immune response to counteract the high mortality due to cancer. Here we compared the immunogenicity of Primary Effusion Lymphoma (PEL) cell death induced by anticancer drug Bortezomib (Velcade) and Tyrphostin AG 490, a Janus Activated Kinase 2/signal trasducer and activator of transcription-3 (JAK2/STAT3) inhibitor. We show that both treatments were able to induce PEL apoptosis with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 35 publications
8
54
0
1
Order By: Relevance
“…More recently, we have shown that the AG490-mediated PEL cell death was immunogenic, inducing the exposure of Heat Shock Proteins (HSPs) on the surface of dying cells. In the same experiments, we noticed a reduction of total HSP expression in PEL cells following AG490 treatment [9]. In the present study, we more thoroughly explored the effect of AG490 on HSP response and investigated, in particular, the effect of AG490 on the expression Heat Shock Transcription Factor 1 (HSF1), the most important transcription factor regulating HSP expression [10].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…More recently, we have shown that the AG490-mediated PEL cell death was immunogenic, inducing the exposure of Heat Shock Proteins (HSPs) on the surface of dying cells. In the same experiments, we noticed a reduction of total HSP expression in PEL cells following AG490 treatment [9]. In the present study, we more thoroughly explored the effect of AG490 on HSP response and investigated, in particular, the effect of AG490 on the expression Heat Shock Transcription Factor 1 (HSF1), the most important transcription factor regulating HSP expression [10].…”
Section: Introductionmentioning
confidence: 70%
“…These findings indicate that such combination could be exploited to improve the outcome of anti-cancer therapy against PEL. In a previous study we showed that AG490 induces an immunogenic cell death in PEL cells [9] and other authors have also reported that AG490 is able to counteract the cancer-mediated immune suppression, that correlates with STAT3 hyper-activation in dysfunctional DC cultured in the presence of tumor released factors [24,36] or present in the tumor environment [23]. Based on this knowledge, we suggest that AG490, especially if combined with autophagy inhibitors, could represent an ideal anticancer therapy against PEL as well as against other tumors characterized by the release of factors that activate STAT3 in an autocrine and paracrine fashion.…”
Section: Discussionmentioning
confidence: 96%
“…158 In both examples, the ability of a specific agent (e.g., oxaliplatin, cyclophosphamide) but not one of its alike (e.g., cisplatin, melphalan) to drive ICD can be explained by the differential activation of ER stress (and hence differential exposure of CALR in the course of RCD). 100,[157][158][159] Well established ICD inducers include commonly employed anticancer chemotherapeutics such as: (1) (6) bortezomib, a proteasomal inhibitor approved for the therapy MM and mantle cell lymphoma (MCL); [171][172][173][174][175][176][177][178][179][180][181] (7) cyclophosphamide, a DNA-alkylating agent approved for use in patients with chronic myeloid leukemia (CML), AML, ALL, chronic lymphocytic leukemia, MM, ovarian carcinoma, breast carcinoma, mycosis fungoides, lymphoma, neuroblastoma, and retinoblastoma; 177,[182][183][184][185][186][187][188][189][190][191] and (8) oxaliplatin, a platinum-derivative licensed for the therapy of advanced colorectal carcinoma in combination with 5-fluorouracil and folinic acid. 156,157,[192][193][194][195][196][197][198] Moreover, there is some evidence that microtubule-targeting agents including taxanes and vinca alkaloids (which are commonly used for the treatment of multiple carcinomas) can stimulate ICD.…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenic cell death is a drug-induced process, 49-52 first described after doxorubicin treatment in 2005 by Casares et al 53 The drug most known for its ability to induce immunogenic cell death in the context of myeloma treatment is bortezomib 40,48,54,55 (used in 17 of 18 patients in our cohort), but other drugs used in our myeloma-conditioning regimens prior to allogeneic HSCT, such as melphalan [56][57][58] and cyclophosphamide, 59,60 can act in this way. After treatment, the dying tumor cells secrete or translocate "danger-associated molecular patterns" (DAMPs) to the cell surface.…”
Section: Discussionmentioning
confidence: 84%